The effect of internal mammary lymph node biopsy on the therapeutic decision and survival of patients with breast cancer. Issue 10 (October 2015) - Ozmen, V.; Ozcinar, B.; Bozdogan, A.; Eralp, Y.; Yavuz, E.; Dincer, M.
Abstract Background The role of internal mammary lymph node biopsy (IMLNB) is still being discussed in breast cancer treatment. The aim of this study was to investigate the role of IMLNB on adjuvant therapy and survival of patients with breast cancer. Pateints and methods The data of 72 patients with clinically negative axilla and IMLNB were evaluated. IMLNB was performed either through a small separate intercostal incision or from the same incision for tumor resection or mastectomy by using both blue dye and radioisotope. Pathological analysis was performed on formalin-fixed paraffin-embedded tissues. Results Ten of the patients (14%) were IMLNB-positive. The axillary sentinel lymph node and IMLN were negative in most of the patients (52.8%). In one patient (1.4%), the axilla was negative but the IMLNB was positive. IMLNB changed the pathologic stage in eight patients (11%). Adjuvant internal mammary radiotherapy was added to the treatment protocol for 10 patients due to IMLNB positivity and adjuvant chemotherapy was added in for only one patient with negative axilla. The factors found to be related with IMLN positivity were SLN positivity (p = 0.033), mastectomy (p = 0.022), and the number of resected IMLN ≥2 (p = 0.040). The median follow-up time was 115.5 months (range, 30–162 months). The ten-year overall survival (OS) rate was 86%. Systemic metastasis (p = 0.007), SLNB positivity (p < 0.001), and IMLNB positivity (p = 0.005) were statistically related to overall survival. Conclusion IMLNB positivity in patients with breast cancer changed the pathologic stage and adjuvant treatment modalities of patients and also adversely affected the overall survival.